2019
DOI: 10.1093/nar/gkz783
|View full text |Cite
|
Sign up to set email alerts
|

Translational recoding: canonical translation mechanisms reinterpreted

Abstract: During canonical translation, the ribosome moves along an mRNA from the start to the stop codon in exact steps of one codon at a time. The collinearity of the mRNA and the protein sequence is essential for the quality of the cellular proteome. Spontaneous errors in decoding or translocation are rare and result in a deficient protein. However, dedicated recoding signals in the mRNA can reprogram the ribosome to read the message in alternative ways. This review summarizes the recent advances in understanding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 159 publications
(194 reference statements)
5
72
1
Order By: Relevance
“…where N is a stretch of three identical nucleotides, W is either AAA or UUU, and Z ≠ G. The linker region is less well-defined, but typically is short (1 -12 nt long) and is thought to be important for determining the extent of -1 PRF in a virus-specific manner. The function of the downstream secondary structure is to induce elongating ribosomes to pause, a critical step for efficient -1 PRF to occur [reviewed in (9)]. The generally accepted mechanism of -1 PRF is that the mRNA secondary structure directs elongating ribosomes to pause with its A-and P- suggesting that it may present a target for small molecule therapeutics (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…where N is a stretch of three identical nucleotides, W is either AAA or UUU, and Z ≠ G. The linker region is less well-defined, but typically is short (1 -12 nt long) and is thought to be important for determining the extent of -1 PRF in a virus-specific manner. The function of the downstream secondary structure is to induce elongating ribosomes to pause, a critical step for efficient -1 PRF to occur [reviewed in (9)]. The generally accepted mechanism of -1 PRF is that the mRNA secondary structure directs elongating ribosomes to pause with its A-and P- suggesting that it may present a target for small molecule therapeutics (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…This complex mechanism requires special trans-acting protein factors (Sec insertion sequence binding protein 2 and Sec-specific translation elongation factor) and a cis-acting Sec insertion sequence (SECIS) element (a stem-loop structure located immediately downstream of the in-frame UGA codon at which Sec is incorporated) [9,44]. For the decoding of a stop codon by near cognate tRNA, genomic analyses, and profiling studies of human genes have found several potential readthrough candidates [9] some of which were confirmed experimentally. About 4% of malate dehydrogenase is physiologically extended by translational readthrough, with arginine and tryptophan being co-encoded by the UGA stop codon [45].…”
Section: Discussionmentioning
confidence: 99%
“…The first phenomenon does not alter the translational reading frame and extends the polypeptide C-terminally [9]. Stop codon can be decoded as a sense codon by either a near-cognate tRNA (tRNA with anticodons that have a single mismatch upon pairing to a stop codon) or the specialized cognate tRNAs (tRNAs with an anticodon that is complementary to the stop codon), such as tRNA Sec [9]. Both of these recoding events would result in the full-length ALDH3B2 expression (466 amino acids (aa), molecular weight around 53 kDa; longer variant shown in Figure 1).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations